2017
DOI: 10.1111/ele.12795
|View full text |Cite
|
Sign up to set email alerts
|

Relative size predicts competitive outcome through 2 million years

Abstract: Competition is an important biotic interaction that influences survival and reproduction. While competition on ecological timescales has received great attention, little is known about competition on evolutionary timescales. Do competitive abilities change over hundreds of thousands to millions of years? Can we predict competitive outcomes using phenotypic traits? How much do traits that confer competitive advantage and competitive outcomes change? Here we show, using communities of encrusting marine bryozoans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 31 publications
(51 reference statements)
5
46
0
Order By: Relevance
“…Our win‐lose overgrowth data have previously been published (Liow et al. , ), but here, we include “draws” as well (reciprocal overgrowth and standoffs), not least because they represent 30% of marginal battles in our data. As previously discussed (Liow et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our win‐lose overgrowth data have previously been published (Liow et al. , ), but here, we include “draws” as well (reciprocal overgrowth and standoffs), not least because they represent 30% of marginal battles in our data. As previously discussed (Liow et al.…”
Section: Methodsmentioning
confidence: 99%
“…In the same system, zooid size (i.e., the size of the individual modules of the colony) was shown to be a predictor of overgrowth outcomes: species with relatively large zooids have the upper hand (Liow et al. ). However, not only is there variation in the outcomes of such spatial competition not fully explained by zooid size, but other traits are also thought to affect spatial competition (Centurion and Gappa , Taylor ).…”
Section: Introductionmentioning
confidence: 99%
“…The Plio-Pleistocene of the Wanganui Basin contains rich bryozoan faunas that are currently being studied as exemplars of the macroevolutionary dynamics of ecological interactions through geological time (Liow et al , 2017. While the taxonomy of the cyclostomes in the sequences has received little attention for evaluation, it is apparent that most of the cheilostomes present are species still living in New Zealand waters.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Gordon et al (2009) reported that 65% of the Pliocene bryozoan species of New Zealand are still extant. Ongoing research focusing on ecological interactions among bryozoans from the Wanganui Basin (Liow et al , 2017 has prompted taxonomic revision for some taxa (e.g., Di , resulting in a reduction of this percentage. In addition, these studies have revealed the presence of three new species, which are described here: Buskia waiinuensis sp.…”
mentioning
confidence: 99%
“…), as well as life history variation (Marshall and Monro ) and spatial competition (Liow et al. ; Liow et al. ).…”
Section: Methodsmentioning
confidence: 99%